Predicting and measuring thermal conductivity in carbonepoxy unidirectional tape and textile reinforced composites - Hind, Simon (University of Ottawa (Canada), 2010)
The directional thermal conductivity of composite parts and moulds has a strong effect on out-of autoclave manufacturing operations. Limited thermal conductivity and variability data is available for composites made from carbon fibres that are widely used in mould and aircraft construction. A summary of experimental measurements and directional thermal conductivity models for carbon/epoxy composite materials is presented. Experimental data were collected for AS4 fibre unidirectional tape prepreg and T300 fibre unidirectional non-woven and plain weave textile reinforced composites. Lamination sequences included [0°]n, [0°/90°]n, [0°/90°/0°] n, [0°/60°/-60°]n and [0°/+45°/-45°/90°] n. Manufacturing methods included hybrid hand-layup and autoclave curing. Variability is quantified in all cases. Techniques for the predictive modeling of directional thermal conductivity are assessed. Classical lamination theory and models of conductivity for homogeneous assemblies of aligned fibres were used to determine thermal conductivity of tape prepreg and thermal properties of textile yarns. Unit cell simulations of textile based composites were performed to quantify the effect of changes in reinforcement geometry and configuration on directional thermal conductivity. A series of steady-state finite element models were developed for non-woven composites, unidirectional and cross-ply, and for plain weave textiles [0°/90°], [0°/90°/0°] n and [0°/+45°/-45°/90°]. Recommendations for the applicability of different modeling methods for the determination of thermal conductivity in composite materials are presented.
Keywords: Engineering, Mechanical.